2018
DOI: 10.1088/1361-651x/aae9ce
|View full text |Cite
|
Sign up to set email alerts
|

A graphite nodule growth model validated by in situ synchrotron x-ray tomography

Abstract: An accurate prediction of ductile cast iron microstructures is crucial for a science-based optimisation of cast component design. The number density and distribution of graphite nodules critically influence the mechanical performance of a component in service. Although models predicting nodule growth have been researched for many years, recent improvements have been impeded by lack of detailed experimental data on nodule growth kinetics for validation. This data has now been made available through in situ obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Overall, it can be concluded that the time‐resolved 3D X‐ray tomography studies conducted so far have captured the dynamic processes of the nucleation, growth, and floating of GPs and highlighted how the degenerate features develop from spheroidal GPs. These findings are crucial for the development of advanced models where some of the simplifying assumptions associated with the traditional solidification models are relaxed 24 …”
Section: Solidificationmentioning
confidence: 99%
“…Overall, it can be concluded that the time‐resolved 3D X‐ray tomography studies conducted so far have captured the dynamic processes of the nucleation, growth, and floating of GPs and highlighted how the degenerate features develop from spheroidal GPs. These findings are crucial for the development of advanced models where some of the simplifying assumptions associated with the traditional solidification models are relaxed 24 …”
Section: Solidificationmentioning
confidence: 99%
“…It is equally important to understand the effect of thermal fluctuations on the local microstructure. Several numerical models have been proposed to describe nodule growth ranging from a 1D spherical coordinate model [37] (based on a uni-nodular approach [38]) to a 3D Phase Field simulation [39]. These models assume uniform spherical nodule growth, degenerate morphologies are not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%